2017
DOI: 10.1111/ecno.12088
|View full text |Cite
|
Sign up to set email alerts
|

How Do Macroeconomic and Bank‐specific Variables Influence Profitability in the Austrian Banking Sector? Evidence from a Panel Vector Autoregression Analysis

Abstract: We examine the determinants of the net interest margin (NIM) and the net fee and commission income ratio (NFCIR) of Austrian banks as well as their interrelationship and whether portfolio separation between loan and deposit categories holds. We describe a conceptual framework for the profit optimization problem faced by banks as a Bertrand game with differentiated products and intrafirm product interactions. We contribute to the literature by factoring in banks’ business models in terms of their balance sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
2
1
Order By: Relevance
“…The oil price found to be significant in our study is contradicted by Yanikkaya et al [51], who could not find a relationship between them. Meanwhile, the significant influence of leverage on NPM, found for IB, contrast the finding of Sigmund et al [52], who could not find a significant relationship in a similar study. Sun et al [53], in their study found no relationship between capital ratio and net interest margin for CBs and net profit margin for IBs in their study to determine the driving bank performance in OIC countries, hence in contrast with our findings that shows an existence of causal relationship between capital adequacy and NIM for CBs, and between NPM for IBs.…”
Section: Long and Short-run Causal Relationshipcontrasting
confidence: 86%
“…The oil price found to be significant in our study is contradicted by Yanikkaya et al [51], who could not find a relationship between them. Meanwhile, the significant influence of leverage on NPM, found for IB, contrast the finding of Sigmund et al [52], who could not find a significant relationship in a similar study. Sun et al [53], in their study found no relationship between capital ratio and net interest margin for CBs and net profit margin for IBs in their study to determine the driving bank performance in OIC countries, hence in contrast with our findings that shows an existence of causal relationship between capital adequacy and NIM for CBs, and between NPM for IBs.…”
Section: Long and Short-run Causal Relationshipcontrasting
confidence: 86%
“…In the paper we decide to adopt the panel vector-autoregression modelling, which so far has been relatively rarely used in macroeconomic studies. Some more recent examples of this method usage may be traced in works of, inter alia, Gnimasoun and Mignon (2016), Aminsano and Geweke (2017), Koop (2017), Sigmund et al (2017) or Thach and Oanch (2018). Surely this Ewa Lechman ISSN 2071-789X RECENT ISSUES IN ECONOMIC DEVELOPMENT method has certain advantages and limitations as always when qualitative in nature process are intended to be captured in numbers.…”
Section: Methodological Approachmentioning
confidence: 99%
“…The creation of such a model treatment allows for dynamic or static dependencies that may arise among the examined countries. Additionally, it can tackle the existence of potential heterogeneity in the estimated coefficients on the variables examined (Sigmund et al, 2017;Sigmund and Ferstl, 2019;Ozcan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%